Eficiência da Receita Federal : análise estocástica em painés de dados - Silva, Edair Ribeiro da (2007)
The objective of this paper is to study the efficiency of the Secretaria da Receita Federal (SRF), from 2001 to 2006. The studied efficiency corresponds to the concept of technical efficiency in a boarding of revenue frontier, in other words, the gauging of the maximum of levies, given the available economic information, in contraposition to the done levying. Recent econometrical studies point with respect to the method of stochastic frontier of production, which was used in panel data. The units of the SRF had been grouped in 107 localities. The method of stochastic frontier was adequate to the study. The analized parameters had been significant and the results had not allowed to false the existence of a frontier. Diverse levels of efficiency between the studied localities had been found, which had varied between 53,6 to 80,0% on Fiscal Regions, acording to a choiced model. In the period it had increment of the SRF efficiency, around 0,1% a year. Units with betterhuman structure and with larger productivity obtained best results. The increase of efficiency in SRF contributed for the tax burden increase. This efficiency increase can contribute for the healthy reduction of the tax collecting.